HMGB1 contributes to allergen-induced airway remodeling in a murine model of chronic asthma by modulating airway inflammation and activating lung fibroblasts - Hou, Changchun (Cell Mol Immunol, 2015)
The pro-inflammation factor high-mobility group box protein 1 (HMGB1) has been implicated in the pathogenesis of asthma. In this study, we used a murine model of chronic asthma to evaluate the effects of HMGB1 on airway remodeling. Female BALB/c mice were randomly divided into four groups: control, ovalbumin (OVA) asthmatic, OVA+isotype antibody and OVA+anti-HMGB1 antibody. Anti-HMGB1 antibody therapy was started on day 21 and was administered three times per week for 6 weeks before intranasal challenge with OVA. In this mouse model, HMGB1 expression is significantly elevated. The anti-HMGB1 antibody group exhibited decreased levels of immunoglobulin E (IgE) and inflammatory mediators and reduced inflammatory cell accumulation, airway hyperresponsiveness (AHR), mucus synthesis, smooth muscle thickness and lung collagen content compared with the OVA groups. Treatment with HMGB1 increased proliferation, migration, collagen secretion and α-smooth muscle actin (SMA) expression in MRC-5 cells. Treatment with the HMGB1/IL-1β complex significantly increased the expression and secretion of transforming growth factor (TGF-β1), matrix metalloproteinase (MMP)-9 and vascular endothelial growth factor (VEGF). Altogether, these results suggest that blocking HMGB1 activity may reverse airway remodeling by suppressing airway inflammation and modulating lung fibroblast phenotype and activation.